Efficacy of Human Fibrinogen-Thrombin Patch (TachoSil) Clinical Application in Upper Gastrointestinal Cancer Surgery. (1st November 2016) - Marano, Luigi; Di Martino, Natale
ABSTRACT: Background: Previous studies investigated the efficacy and applicability of tissue adhesives in gastrointestinal surgery while no evidence is available to date about a novel compound, TachoSil (Takeda, Zurich, Switzerland). The primary aim of this observational study was to assess the effect of new fibrin sealant on the incidence of postoperative complications in a homogeneous group of patients submitted to upper gastrointestinal surgery for cancer. Methods: Two cohorts of 28 and 34 patients undergoing upper gastrointestinal for surgery were compared. In the first cohort, the anastomotic site was treated with TachoSil fibrinogen-thrombin-collagen patches and in the second no collagen sponge or any other hemostatic sealant was used. Postoperative complications and outcomes as well as postoperative biochemical parameters were analyzed. Results: Postoperative complications occurred in 12 patients (35.3%) and 2 patients (7.1%) in control and collagen sponge group respectively (χ 2 = 3.539, p < 0.05), with no anastomotic leakage in the collagen sponge group. A binary logistic regression analysis showed that the nonuse of collagen sponge [odds ratio (OR) = 0.025, 95% confidence interval (CI) = 0.001–0.457, p = 0.01] was independently associated with postoperative complication occurrence. Conclusions: The addition of fibrinogen-thrombin-collagen sponge patch may reduce postoperative complication rate after upper gastrointestinal surgery for cancer. Further study to delineate the role of TachoSil in gastrointestinal surgery are also needed to demonstrate improved effectiveness and applicability.